Effect of asymmetric warming on rice (Oryza sativa) growth characteristics and yield components under a free air temperature increase apparatus - XIE, XIAOJIN; ZHANG, YAOHONG; WANG, LIN; YANG, XIHUA; YU, QIANG; BAO, YUNXUAN (The Indian Journal of Agricultural Sciences, 2017)
Climate warming shows great diurnal variations with higher warming rate at nighttime, and consequently causes significant impacts on rice growth and grain yield. The objective of this study was to determine the effects of asymmetric warming (all-day warming, AW; daytime warming from 7:00 to 19:00, DW; and nighttime warming from 19:00 to 7:00, NW; and a control, CK) on rice growth characteristics andyield. Two bucket warming experiments were performed in Nanjing in Jiangsu Province, China under Free Air Temperature Increases (FATI) in 2013 and 2014.< The daily mean temperatures in the rice canopy in the AW, DW and NW plots were 2.0°C, 1.1°C and 1.3°C higher, respectively, than those in the CK plots. Asymmetric warming reduced the maximum tillers and effective tillers in the order CK>DW>NW>AW. In the AW, DW and NW treatments, the effective tillers were decreased by18.57%-37.77% in both years. Asymmetric warming also decreased plant height, the Absolute Growth Rate (AGR), the Soil and Plant Analyzer Development (SPAD) value, the Leaf Area Index (LAI) and the Net Photosynthetic Rate (Pn). The order of the plant height and Pn values were also in the order CK>DW>NW>AW. The warming treatments affect the length of rice growth. The length from the transplanting date to the heading date was shortened by 3.5 days, 2.5 days and 3.0 days on average in the AW, DW and NW plots, respectively, in both years, while the length from the heading date to the maturation date did not show obvious changes. The aboveground biomass in the maturation stage declined by 13.38%, 3.56% and 6.22%, and the grain yield was decreased by 10.07%, 5.06% and 7.89% on average in the AW, DW and NW plots, respectively, in both years. There was a decreasing trend in the panicle number, grain number per panicle and grain filling rate, whereas irregular changes in the 1000-grain weight were observed in the warmed plots. Our results suggested that under the predicted climate warming, rice productivity would be further declined in the Yangtze River Basin.